1994
DOI: 10.1042/bj2990489
|View full text |Cite
|
Sign up to set email alerts
|

New isoforms of Ca2+/calmodulin-dependent protein kinase II in smooth muscle

Abstract: Four novel isoforms of Ca2+/calmodulin-dependent protein kinase II (CaM kinase II) were found in rat aorta smooth muscle. Two of them were related to gamma-isoform of brain CaM kinase II (gamma-a). Differences in the primary structure of these isoforms were located in the variable region. One of them (gamma-b) contained 23 unique amino acid residues, whereas the other (gamma-c) did not contain this sequence. Both isoforms lacked the two segments (Val-316 to Gln-337 and Lys-353 to Leu-362) present in gamma-a. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 31 publications
1
26
0
Order By: Relevance
“…CamKII is one of the most abundant kinases in the central nervous system (CNS), comprising as much as 2% of total forebrain protein (Kelly, 1991;Schulman and Hanson, 1993). Initially isolated as a multimeric holoenzyme of ␣ and ␤ subunits, recent studies have identified two additional subunits, ␦ and ␥, as well as a series of alternatively spliced isoforms (Tobimatsu et al, 1988;Tobimatsu and Fujisawa, 1989;Benson et al, 1991;Mayer et al, 1993;Zhou and Ikebe, 1994). The ␣CamKII and ␤CamKII subunits are the most abundant throughout the brain and are localized within the same excitatory neuronal populations as BDNF mRNA, including all subfields of the hippocampus and the dentate gyrus as well as the amygdala and most layers and regions of cortex (Erondu and Kennedy, 1985;Ouimet et al, 1984;Benson et al, 1992b).…”
mentioning
confidence: 98%
“…CamKII is one of the most abundant kinases in the central nervous system (CNS), comprising as much as 2% of total forebrain protein (Kelly, 1991;Schulman and Hanson, 1993). Initially isolated as a multimeric holoenzyme of ␣ and ␤ subunits, recent studies have identified two additional subunits, ␦ and ␥, as well as a series of alternatively spliced isoforms (Tobimatsu et al, 1988;Tobimatsu and Fujisawa, 1989;Benson et al, 1991;Mayer et al, 1993;Zhou and Ikebe, 1994). The ␣CamKII and ␤CamKII subunits are the most abundant throughout the brain and are localized within the same excitatory neuronal populations as BDNF mRNA, including all subfields of the hippocampus and the dentate gyrus as well as the amygdala and most layers and regions of cortex (Erondu and Kennedy, 1985;Ouimet et al, 1984;Benson et al, 1992b).…”
mentioning
confidence: 98%
“…1, A, right panel and B). CaMKII isoforms ␥ and ␦ are reported to be expressed in arteries (22,23), therefore we performed qRT-PCR to identify which isoforms are up-regulated after carotid ligation. 14 days after surgery, CaMKII␦ mRNA was increased by 42.6%ϩ3.6% (p Ͻ 0.05) whereas CaMKII␥ mRNA was unchanged in response to ligation (Fig.…”
Section: Camkii Expression In the Neointima After Carotid Ligation-mentioning
confidence: 99%
“…In VSMCs, freeCaM binding with Ca 2+ could accelerate the formation of the CaM-CaM related kinase II (CaMK II) complex, a ubiquitous multifunctional serine/threonine kinase expressed in VSMCs as multimers of γ-and/or δ-sun units [29] , and increase MLCK activity and MLC20 phosphorylation, which contribute to vascular contraction [30] . However, Ca 2+ release located next to cytomembranes, also known as Ca 2+ spark, triggers the formation of STOCs [31] and activates the large conductance calcium activated potassium channel (BK Ca ), which at least partially contributes to the vascular hyporeactivity observed after hemorrhagic shock [32] .…”
Section: Discussionmentioning
confidence: 99%